Antibacterial ability of supported silver nanoparticles by functionalized hydroxyapatite with 5-aminosalicylic acid. (February 2018) - Lazić, Vesna; Smičiklas, Ivana; Marković, Jelena; Lončarević, Davor; Dostanić, Jasmina; Ahrenkiel, S. Phillip; Nedeljković, Jovan M.
Abstract: Antimicrobial performance of silver nanoparticles supported by functionalized hydroxyapatite with 5-aminosalycile acid was tested against Gram-negative bacteria E. coli, Gram-positive bacteria S. aureus and yeast C. albicans . Thorough characterization of materials (electron microscopy, nitrogen adsorption–desorption isotherms, diffuse reflectance spectroscopy) followed each step during the course of nanocomposite preparation. Synthesized powder consists of rod-like hydroxyapatite particles (40–60 × 10–20 nm, length × diameter) decorated with nano-sized spherical silver particles whose content in nanocomposite was found to be 1.9 wt.-%. Concentration- and time-dependent bacterial reduction data indicated that use of silver nanoparticles even at concentration as low as 1 μg mL −1 lead to complete reduction of both bacteria ( E. coli and S. aureus ). On the other hand, non-toxic behavior of nanocomposite in broad concentration range (0.05–2.0 mg mL −1 ) was found towards C. albicans . Successful inactivation of E. coli and S. aureus in five repeated cycles proved that synthesized nanocomposite can perform under long-run working conditions. Graphical abstract: Highlights: New synthetic approach for preparation of Ag – hydroxyapatite nanocomposites. Functionalization of hydroxyapatite with 5-amino salicylic acid. Efficient inactivation of E. coli and S. aureus over synthesized nanocomposite. Preserved antibacterial ability of nanocomposite under long-run working conditions.